A pediatric case of inverted papilloma in the bladder detected by screening ultrasonography based on findings from a school medical checkup - Taiju Hyuga; Shigeru Nakamura; Kazuya Tanabe; Taro Kubo; Hitomi Niijima; Yuta Kawahara; Waka Nakata; Rieko Furukawa; Mio Sakaguchi; Akira Shimada; Mitsuru Matsuki; Toshiro Niki; et al. (Journal of Pediatric Surgery Case Reports, 2022)
We report a case of a girl with inverted papilloma of the urinary bladder, which was detected by ultrasonographic screening based on the findings of a school medical checkup. The case was an 11-year-old girl. She was diagnosed as having occult hematuria and proteinuria by a school medical checkup. Abdominal ultrasonography revealed a high echoic lesion protruding into the bladder. Cystoscopic findings showed a thumb fingertip-sized papillary pedunculated tumor located at the trigone in the bladder. Transurethral resection was performed and pathological examination rendered the diagnosis of inverted papilloma of the urinary bladder. Eight cases of bladder inverted papilloma in children have been reported including our case. This is the first case detected asymptomatically based on a school medical checkup. We believe that ultrasound screening of the urinary tract should be considered when treating patients with positive occult hematuria, such as in a school medical checkup.